2022
DOI: 10.3390/toxins14020133
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Approach Gives Insights into Ig-like Fold Containing Proteins in Vibrio parahaemolyticus: A Focus on the Fibrillar Adhesins

Abstract: Immunoglobulin-like (Ig-like) fold domains are abundant on the surface of bacteria, where they are required for cell-to-cell recognition, adhesion, biofilm formation, and conjugative transfer. Fibrillar adhesins are proteins with Ig-like fold(s) that have filamentous structures at the cell surface, being thinner and more flexible than pili. While the roles of fibrillar adhesins have been proposed in bacteria overall, their characterization in Vibrio parahaemolyticus has not been established and, therefore, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Possibly, it is important in the protection against unfolding of the previously mentioned OmpA and other OMPs. The association with two immunoglobulin-like domain-containing proteins is seen, which are often surface proteins involved in cell-to-cell recognition, adhesion, biofilm formation, and conjugative transfer [ 56 , 57 ]. These domains are widely present in numerous proteins, and several have been identified in V. parahaemolyticus , such as adhesive factor VpadF [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, it is important in the protection against unfolding of the previously mentioned OmpA and other OMPs. The association with two immunoglobulin-like domain-containing proteins is seen, which are often surface proteins involved in cell-to-cell recognition, adhesion, biofilm formation, and conjugative transfer [ 56 , 57 ]. These domains are widely present in numerous proteins, and several have been identified in V. parahaemolyticus , such as adhesive factor VpadF [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association with two immunoglobulin-like domain-containing proteins is seen, which are often surface proteins involved in cell-to-cell recognition, adhesion, biofilm formation, and conjugative transfer [ 56 , 57 ]. These domains are widely present in numerous proteins, and several have been identified in V. parahaemolyticus , such as adhesive factor VpadF [ 56 , 57 ]. Association with toxin gene ccdB indicated the importance of the toxin-antitoxin (TA) system ccdA-ccdB, consisting of the stable toxin ccdB and less stable antitoxin ccdA to neutralize the toxin.…”
Section: Discussionmentioning
confidence: 99%
“…In a computer simulation study, four novel fibrillar adhesin-like proteins, WP_005477759.1, WP_005480168.1, WP_005489282.1, and WP_005490731.1, were identified in Vibrio parahaemolyticus. A previous study analyzed the binding of 277 compounds to these four proteins and found that, except for the slightly weaker binding of WP_005480168.1, the binding of obacunone to the remaining three ranked in the top five, revealing its potential to inhibit the virulence of Vibrio parahaemolyticus on the host [64].…”
Section: Effects On Vibrio Parahaemolyticusmentioning
confidence: 99%